Predictive factors of outcomes in patients with AL amyloidosis treated with daratumumab. Issue 1 (15th November 2021) - Szalat, Raphael E.; Gustine, Joshua; Sloan, J. Mark; Edwards, Camille V.; Sanchorawala, Vaishali
Abstract: Daratumumab as a single agent (sDARA) or in combination with chemotherapies (cDARA) leads to impressive hematologic and organ responses in AL amyloidosis. However, predictive factors associated with outcomes, and optimal duration of therapy remain unclear. We analyzed 107 patients with AL amyloidosis treated with daratumumab between 2017 and 2020. The median overall survival (OS) was not reached while the median major organ deterioration progression free survival (MOD‐PFS) was 36 months in the sDARA cohort and not reached in the cDARA cohort, respectively. Hematologic response > VGPR was achieved in 81% of patients receiving sDARA and 86% of patients treated with cDARA. Several predictive factors were identified on a univariate analysis, including NTproBNP >8500 pg/mL but only achievement of at least VGPR and presence of 1q21 gain were independently associated with MOD‐PFS and OS on a multivariate analysis. Finally, patients receiving > 12 cycles had significantly longer MOD‐PFS (30 vs.13 months; ( p = .0018) and OS (NR vs. 15 months; p < .0001). NTproBNP > 8500 pg/mL, presence of 1q21 gain and shorter duration of therapy (≤ 12 cycles) are strong negative predictive factors for outcomes with daratumumab therapy in AL amyloidosis.